Acute changes in clinical breast measurements following bra removal: Implications for surgical practice. (March 2015) - Scurr, Joanna; Loveridge, Amy; Brown, Nicola; Mills, Chris
Abstract: Background: Stable measurement of breast position is crucial for objective pre-operative planning and post-operative evaluation. In clinical practice, breast measures are often taken immediately following bra removal. However, research shows that restrictive clothing (such as a bra) can cause acute anatomical changes, leading to the hypothesis that clinical breast measures may change over time following bra removal. This cross-sectional observational study aimed to provide simple clinical guidelines for the measurement of breast position which account for any acute changes in breast position following bra removal. Methods: Thirteen participants of varying breast sizes had markers attached to their thorax and nipples to determine clinical measures of sternal notch to nipple distance, internipple distance, breast projection, and vertical nipple position. The positions of these landmarks were recorded using a motion capture system during 10 min of controlled sitting following bra removal. Results: Internipple distance and breast projection remained unchanged over 10 min, while the resultant sternal notch to nipple distance extended by 2.8 mm in 299 s (right) and 3.7 mm in 348 s (left). The greatest change occurred in the vertical nipple position, which migrated an average of 4.1 mm in 365 s (right) and 6.6 mm in 272 s (left), however, for one participant vertical migration was up to 20 mm. Conclusions: Internipple distance and breast projection can be measured first following bra removal, followed by sternal notch to nipple distance, any measures associated with the vertical nipple position should be made more than 6 min after bra removal. These guidelines have implications for breast surgery, particularly for unilateral reconstruction based on the residual breast position.